SYNTHESIS AND CHARACTERISATION OF FATTY HYDRAZIDE DERIVATIVES TO ACT AS NAPHTHENATE INHIBITOR-DEMULSIFIER - BORHAN, NOORAZLENAWATI (2021)
Chemical enhanced oil recovery (CEOR) injection using alkaline, surfactant, and polymer (ASP) into the reservoir formed a microemulsion system which consists of sodium carboxylate soaps and ASP fluids; thus, naphthenate inhibitor (NI)–demulsifier were developed to impede this type of microemulsion. Four (4) synthesis compounds were produced with the initial formation of monomethyl maleate (MMM) from esterification of maleic acid anhydride (MAH) and methanol (MeOH) at a temperature of 55-60 ℃ and continue to react with fatty hydrazide (FH) in a solvent of 1:1 methyl isobutyl ketone (MIBK) and N,N-dimethylformamide (DMF) at a temperature of 80-90 ℃. The yield for palmitic amide-MMM, i.e. product A from the reaction of molar ratio 1:1 between palmitic hydrazide and MAH, was 58%. The yield for palm fatty amide-MMM, i.e. product B1 from the reaction of molar ratio 1:4 between palm fatty hydrazide and MAH, was 66%, while product B2 yield from the molar ratio 1:1 was 32%. The yield for stearic amide-MMM, i.e. product C from the reaction of molar ratio 1:1 between stearic hydrazide and MAH, was 60%. The characterisation for products A, B1, B2 and C were via fourier transform infrared (FTIR), nuclear magnetic resonance (NMR), mass spectroscopy (MS/MS), and elemental analyser-CHNSO. Product B1 was soluble in most solvent candidates and used in two (2) formulations using solvesso 150. NI-demulsifiers A and B tested in bottle tests showed elevated temperature, extended separation time, and increased concentration of NI-demulsifiers successfully reduced the basic sediment and water (BS&W) of less than 0.5% at atmospheric pressure and a low shear rate of 300 rpm. Multifunctional Mini-Flow Loop (MMFL) tested at a 4.5 bar, and a high shear rate of 13,500 rpm showed at concentration 25 ppm, NI- demulsifier B had decreased water in crude oil (W/O) by 0.9%-2.2% from high content W/O, i.e. 13% and prevented solid deposition. A commercial demulsifier was less efficient to decrease W/O by only 2-7%. Thus, the conclusion was that NI-demulsifier B showed superior performance as compared to commercial demulsifier.